Significantly elevated strength of W-Ni3Al alloy by adding trace boron element. (February 2023) - Mao, Ruipeng; Xiang, Daoping
Abstract: W-Ni3 Al alloys have potential application in kinetic energy penetrator, but there are some problems such as high sintering temperature, large tungsten grain size, and poor mechanical properties. In this study, fine-grained W-Ni3 Al-B alloys with excellent mechanical properties were successfully fabricated at a low temperature of 1150 °C by adding trace boron powder (B) and using spark plasma sintering (SPS). For the addition of B in the W-Ni3 Al alloys, the low melting point B2 O3 phase was formed and its thermite reaction released extra heat, promoting the sintering of the alloys. However, with the increasing of B content (0.1–0.7 wt%), the more hard brittle phases were formed, damaging the strength of sintered alloys; at the same time, the more B2 O3 phase was evaporated due to the more released heat, causing occurrence of pores. Among all B-containing W-Ni3 Al alloys, the 0.1B alloy exhibited the optimal mechanical properties with the bending strength of 1375.88 ± 19.20 MPa (higher 99.32% than that of the 0B alloy) and a high hardness value of 71.6 ± 0.29 HRA. By analyzing 0.1B alloy's microstructure, its good mechanical properties were related to the small tungsten grain size, heterostructural binder phase, minimal formation of hard brittle phases, dislocation movements being obstructed by the Al2 O3 phase, and the tungsten transgranular cleavage fracture mode. Highlights: W-Ni3 Al-B alloys were fabricated at a low temperature of 1150 °C. The formed B2 O3 with low melting point and its thermite reaction facilitated alloy's sintering. The 0.1B alloy had the best comprehensive mechanical properties. The improved properties of the alloy originated from synergetic reinforcement.